Kinetics of Free Radical Polymerization of Methylacrylate Initiated by Potassium Peroxomonosulphate and Tetrabutyl Phosphonium Chloride - DAMODARKUMAR, S.; PERUMAL, A. (Asian Journal of Chemistry, 2010)
In present studies, the systematic study of kinetics and mechanism of phase-transfer catalyzed free radical polymerization of methylacrylate (MA) water-soluble initiator potassium peroxomonosulphate (PMS) coupled with tetrabutyl phosphonium chloride (TBPC) catalyst system in ethyl acetate/water bi-phase in the temperature range 45-55°C at fixed pH and ionic strength is reported. The rate of polymerization increases with an increase in concentration of MA, PMS and phase-transfer catalyst, viz., tetrabutyl phosphonium chloride. It was observed that the rate of polymerization (Rp) is proportional to [MA]1.0, [KHSO5–]0.5 and [TBPC]0.5. A suitable kinetic scheme has been proposed to account for the experimental observations and its significance was discussed.